The Correlation Between The Students' Motivation and The English Proficiency - Endang Yuliani Rahayu (Universitas Stikubank, 2002)
This article is based on the research that has just been conducted by the writer. It is proposed to find out the correlation between students' motivation and English proficiency, further more this article will describe store about the students' motivation. Applying the Karl Pearson's product moment theory, the writer could find the positive correlation. The respondents of this research is the SI degree students of the Information Technology Faculty.